ANALISA PERBANDINGAN METODE SEGMENTASI CITRA PADA CITRA MAMMOGRAM - Toni Arifin (LPPM Universitas Bina Sarana Informatika, 2016)
AbstractCancer is a desaeas with a high prevalence in the world. As many 8,2 million people died of cancer. The prevalence of cancer was happened in woman that is breast cancer. Breast cancer is a malignancy derived from grandular cells, gland duct and supporting the breast tissues. There are many ways of detecting the presence of breast cancer which one is mammography test that aims to examine the human breast using low-dose X-rays. Observation mammography results in the form of mammogram images can be done with image processing, in this way the process of observation is not take a long time and error in the observation can be reduced. One of the process image processing is image segmentation, the step of image segmentation is an important in image analysis there force is needed method in process of image sementation. This observation is aims to analyze comparison of two image segmentation methods of mammogram images that is using Watershed method and Otsu method after that it will see the quality of image by calculating the signal to noise ratio and timing run of each method. The result of this observation is showed that the signal to noise ratio on the Watershed method 7,475 dB and Otsu method 6.197 dB and the conclution is Watershed method is better than Otsu method, whereas if viewed the timing run Watershed method 0,016 seconds is more faster than Otsu method.